Joining farmers’ cooperatives leads to equitable poverty reduction in China – empirical evidence from the rural households survey - Zhang, Ze; Qin, Lijian; Jia, Yu; Li, Yuheng; Hong, Chen; Qin, Wenshuai (Applied Economics, 2025)
Keywords: China; Empirical evidence; Inequality; Poverty; Poverty reduction; Rural poverty; Survey data collection; dept.eco

Will social participation make retirees happier? An empirical study about retirement life in China - Zhao, Luman; Yu, Jia (Journal of Applied Business and Economics, 2025)
How elderlies participate in social activities is a key issue in coping with aging and has an important impact on elderlies’ well-being. This paper examines the effects of different social participation patterns on the happiness of the elderlies in China. The empirical analysis was conducted based on the data from the China Household Finance Survey (CHFS) in 2015. The research results show that compared with reemployment after retirement, community governance is a more common way for retired people to be involved in social activities. We found that reemployment significantly reduces the happiness degree of the retired. Furthermore, this negative effect is more significant in samples without a formal labor contract, relatively lower education level, & senior retired people. In contrast, participating in community governance can significantly improve the happiness level of retirees, which is more essential in the sample of the medium education level and junior retirees.
Keywords: Business; China; Demographic economics; Economics; Empirical research; Labour economics; Life satisfaction; Political science; Psychology; Social psychology; dept.eco

Some determinants of income inequality in Asia and Latin America - Patalinghug, Jason (Valahian Journal of Economic Studies, 2025)
Abstract Income inequality has, in recent years, become a serious issue especially in emerging markets. This paper examines the relationship of income inequality in the Asia-Pacific and Latin America regions to several factors such as gross capital formation, corruption, and per capita gross domestic product (GDP). Using a cross-sectional dataset of 36 countries from both regions for the year 2018 and ordinary least squares regression, the paper shows that gross capital formation and the lack of corruption have a negative and significant relationship with income inequality (as represented by the Gini coefficient). In contrast, per capita GDP has a positive and significant relationship with income inequality. Policymakers who want to rein in income inequality should therefore focus on ways to reduce corruption and increase the formation of capital. This study could be of use for those who are interested in discovering and mitigating the factors that cause income inequality in the developing world.
Keywords: Business; Business informatics; Business management; Demographic economics; Development economics; Economic growth; Economic inequality; Economics; Health care; Income distribution; Inequality; Latin Americans; Mathematics; Political science; dept.eco

What increases the urban–rural gap in firm entry rates? - Kim, Younjun; Orazem, Peter (Small Business Economics, 2025)
Keywords: Agglomeration; Business; Economic geography; Economics; Entrepreneurship; Finance; Firm entry; Human capital; J24; M13; R11; Rural; Urban; dept.eco; peer-reviewed

Corruption, Natural Capital and Economic Development: A Dynamic GMM Analysis - Ang, Joshua; Patalinghug, Jason (Review of Economic Analysis, 2025)
Using a dynamic panel dataset of 150 countries for the period of 2006-2018 and a two-step system GMM estimation model, this paper shows that natural resources have a positive effect on economic development while holding corruption constant. Our findings support the notion that natural resources have a positive effect on the economy of a nation. When a country has less corruption, it improves the appropriation of economic gains from natural resources which serves as natural capital that would drive further capital accumulation and further development. We also find that physical capital, human capital, and freedom from corruption show strong positive effects on economic development, controlling for other economic and institutional variables.
Keywords: Corruption; Dynamic Panel Study; Econometrics; Economic Development; Economics; Human Capital; Language change; Natural Resources; Physical Capital; dept.eco